Language Stylistics and Speech Culture in Sports Journalism - Shavkatova Gulzora Laziz's daughter (European Science Publishing, 2023)
Sports journalism is a field that requires a unique combination of language style and speech culture. Language stylistics refers to how language is used to convey meaning, create atmosphere, and engage an audience. Speech culture includes norms, values and practices that regulate speech behavior in a specific context.
Keywords: style